(untitled) (ЕтноАнтропоЗум/EthnoAnthropoZoom, 2005)
All national ideologies are based on a single fundamental idea, a single ideological burden, which creates the nucleus of the national myth. This idea, in reference to the Greek national myth, is “the tribal invincibility of the genus” or “the continuance of the nation from ancient times to this day”. In a nutshell - it is the idea of the existence of a common language, culture and genus of the Greek people living and breeding in Greece, but also in the wider region of the Eastern Mediterranean, at least from the Bronze Age to this day. Providing proof for this assumption as the principle element of the Greek national myth yields as its product an associating procedure which was completed by the middle of XIX Century.